Land Suitability Evaluation for Upland Rice in Tirtomoyo District, Wonogiri Regency, Indonesia - Suheri, Nur Aida; Mujiyo, Mujiyo; Widijanto, Hery (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2018)
Food cultivation, especially upland rice is needed to fulfill the needs of dryland food. It is necessary to evaluate the suitability of the land so that it can overcome land constraints to increase the productivity of upland rice in Tirtomoyo Regency. The unit of analysis is Soil Mapping Unit based on soil type map using ArcGIS 10.1 and determination of sample point based on purposive sampling method. Data analysis was done by matching between the result of soil characteristic which has been obtained with growth requirement of the upland rice. Based on the results, District Tirtomoyo divided into 4 Soil Mapping Unit. The actual land suitability class for upland rice is moderately suitable (S2) and not suitable (N). Limiting factors include rainfall, slope, erosion hazard, basic saturation, CEC, C-organic, N-total, K2O. Improvement efforts are done by arranging cropping pattern, drainage management, a making of terracing, cover crop planting, implementing organic material, and fertilizing. The suitability class of potential land of upland rice is highly suitable (S1) and marginally suitable (S3).Barbarslot adalah permainan digital yang meniru mesin slot klasik yang biasa ditemukan di kasino. Permainan ini sangat populer karena mudah dimainkan, tidak memerlukan keahlian khusus, dan menawarkan peluang menang yang menggiurkan.